Plasticity in the growth of the chick eye: Emmetropization achieved by alternate morphologies - Wahl, Christina (Vision Res, 2015)
Both refractive properties of the eyes and ambient light conditions affect emmetropization during growth. Exposure to constant light flattens the cornea making chicks hyperopic. To discover whether and how growing chick eyes restore emmetropia after exposure to constant light (CL) for 3, 7, or 11 weeks, we returned chicks to normal (N) conditions with 12 hrs. of light alternating with 12 hrs. of darkness (designated the “R”, or recovery, condition) for total periods of 4, 7, 11, or 17 weeks. The two control groups were raised in CL conditions or raised in N conditions for the same length of time. We measured anterior chamber depths and lens thicknesses with an A-scan ultrasound machine. We measured corneal curvatures with an eight-axis keratometer, and refractions with conventional retinoscopy. We estimated differences in optical powers of CL, R and N chicks of identical age by constructing ray-tracing models using the above measurements and age-adjusted normal lens curvatures. We also computed the sensitivity of focus for small perturbations of the above optical parameters. Full refractive recovery from CL effects always occurred. Hyperopic refractive errors were absent when R chicks were returned to N for as little as one week after 3 weeks CL treatment. In R chicks exposed to CL for 11 weeks and returned to N, axial lengths, vitreous chamber depths and radii of corneal curvatures did not return to normal, although their refractions did. While R chicks can usually recover emmetropia, after long periods of exposure to CL, they cannot recover normal ocular morphology. Emmetropization following CL exposure is achieved primarily by adjusting the relationship between corneal curvature and axial length, resulting in normal refractions.